Association of ocular psuedoexfoliation syndrome with ischemic heart disease, systemic hypertension, and diabetes mellitus Type II in Bundelkhand region: A cross-sectional study - Jitendra Kumar; Archie Gupta; Nilima Takhelchangbam; Pandey, Aditya (Asian Journal of Medical Sciences, 2023)
Background: Studies exploring the links between ischemic heart disease (IHD), arterial hypertension (AH), diabetes mellitus (DM), and pseudoexfoliation syndrome (PEX) have yielded no clear evidence and attributing PEX to any one particular disease. Aims and Objectives: The present study was undertaken to determine the prevalence of PEX syndrome and its association with IHD, AH, and DM at our center. Materials and Methods: The study comprised of participants (n=102) having IHD, AH and DM. Demographic details and clinical history in detail were written down in a structured proforma. Participants in the study were examined for the diagnosis of PEX syndrome with slit lamp bi microscopy as well as direct and indirect ophthalmoscopy. For numerical variables, descriptive statistics comprised mean and standard deviation, and for categorical variables, the percentage of various categories. To compare categorical variables, Chi-square (χ2) test was utilized. Results: The prevalence of PEX in our study came out to be 17.64% (18 of the 102). Patients of PEX were in the age group of 61–70 years, that is, 8 (44.44%) and were males, that is, 11 (61.11%). The percentage of systemic hypertension patients who had PEX syndrome was 35.29% with statistical significant association (χ2=10.9; P=0.001). The percentages of IHD and DM patients with PEX syndrome were 11.76% (χ2=1.214; P=0.270) and 5.88% (χ2=3.718; P=0.053), respectively, the statistical association was a non-significant one. Conclusion: People above 40 years should undergo routine ophthalmological examinations for the detection of PEX Syndrome. Patients diagnosed with hypertension should be given a thorough ophthalmological examination to rule out PEX syndrome.